Ammonoborane-modified chloride solid-state magnesium electrolyte, and preparation method and application thereof
Patent Information
- Application Number
- CN202510555810.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2026-10-30
AI Technical Summary
然而,硼氢化镁普遍具有较差的空气稳定性和高电压稳定性,所以硼氢化镁电解质的操作流程及工艺非常复杂且难以匹配高电压正极材料
[0022]1.本发明利用氨硼烷与四氯铝酸镁之间的相互作用,形成了以镁离子(Mg2+)与四氯铝酸根阴离子(AlCl4-)和氨硼烷小分子(NH3BH3)相互连接的骨架网络结构,该结构表现出优异的镁离子传导能力(室温离子电导率>10-4S/cm),且该氨硼烷与四氯铝酸镁复合固态镁电解质相较于传统硼氢化镁体系具有更好的高压稳定性。基于该氨硼烷与四氯铝酸镁复合固态镁电解质开发的固态镁金属二次电池,在室温条件下实现了正常充放电。
Smart Images

Figure CN123018101A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid-state battery technology, specifically relating to an ammonia borane-modified chloride solid magnesium electrolyte, its preparation method, and its application. Background Technology
[0002] The explosive growth in demand for lithium-ion batteries has raised concerns about the scarcity and uneven distribution of lithium resources, while magnesium metal rechargeable batteries are gaining attention due to their abundant raw material resources. Magnesium metal, in particular, is a highly promising metallic anode material, exhibiting unique advantages such as high volumetric capacity and high safety. However, traditional magnesium metal rechargeable batteries typically use flammable organic ether solvents to formulate the electrolyte, which is prone to gas generation problems due to interfacial side reactions during charging and discharging, and is also susceptible to spontaneous combustion, leading to battery thermal runaway and serious safety hazards. Therefore, it is necessary to develop non-flammable solid magnesium electrolytes to replace flammable liquid organic magnesium electrolytes, further improving the safety and applicability of magnesium metal rechargeable batteries. Furthermore, using solid magnesium electrolytes eliminates the need for battery separators, and optimizing the production process could potentially further improve the energy density of magnesium metal battery systems.
[0003] Currently, reported solid magnesium electrolytes are mainly divided into two categories: polymer systems and inorganic solid systems. Polymer systems typically improve magnesium ion conductivity by adding a small amount of organic solvent as a plasticizer; however, the introduction of organic solvents still poses a flammability hazard. Inorganic solid magnesium electrolyte systems primarily focus on magnesium borohydride. Because the high charge density of magnesium ions makes migration difficult in magnesium borohydride solid materials, researchers have significantly improved the room-temperature magnesium ion conductivity of this type of solid electrolyte system by introducing different amine molecules into magnesium borohydride powder. However, magnesium borohydride generally exhibits poor air stability and high voltage stability, making the operation process and technology of magnesium borohydride electrolytes very complex and difficult to match with high-voltage cathode materials.
[0004] In summary, there is an urgent need to develop novel inorganic solid magnesium electrolyte systems with higher magnesium ion conductivity, higher oxidation stability, and better electrode compatibility for application in solid magnesium metal secondary batteries. Summary of the Invention
[0005] To address the problems existing in the prior art, this invention provides an ammonia borane-modified chloride solid magnesium electrolyte, its preparation method, and its application.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] A chloride solid magnesium electrolyte modified with ammonia borane, wherein the chloride solid magnesium electrolyte is a complex of magnesium tetrachloroaluminate (Mg(AlCl4)2) and ammonia borane (NH3BH3), and its chemical formula is Mg(AlCl4)2·xNH3BH3, 0.1≤x≤5.
[0008] The solid electrolyte is AlCl4 - The anion and NH3BH3 molecule form the structural framework, and the room temperature ionic conductivity can reach 1×10⁻⁶. -4 S / cm, oxidation stability greater than 3.0V vs. Mg / Mg 2+ .
[0009] A method for preparing the ammonia borane-modified chloride solid magnesium electrolyte involves weighing and mixing magnesium tetrachloroaluminate (Mg(AlCl4)2) and ammonia borane (NH3BH3) according to the stoichiometric ratio of the elements in the target solid electrolyte, followed by ball milling to obtain Mg(AlCl4)2·xNH3BH3.
[0010] The weighing and ball milling of the magnesium tetrachloroaluminate (Mg(AlCl4)2) and ammonia borane (NH3BH3) were carried out in an inert gas atmosphere, and the contents of O2 and H2O were both less than 0.01 ppm.
[0011] The ball mill operates at a speed of 100–800 rpm for a time of 0.5–50 h.
[0012] Preferably, the ball mill rotation speed is 200-400 rpm and the ball milling time is 10-30 h.
[0013] An application of the aforementioned ammonia borane-modified chloride solid magnesium electrolyte, specifically its use in the preparation of magnesium electrolytes as magnesium ion transport media for solid magnesium batteries.
[0014] A magnesium battery composite cathode material, comprising an electrolyte and a cathode active material, wherein the electrolyte is the ammonia borane-modified chloride solid magnesium electrolyte.
[0015] The magnesium battery composite cathode material may also contain a conductive agent; wherein the conductive agent is one or more of conductive carbon black, Super-P, Ketjen black, acetylene black, and carbon nanotubes; the cathode active material is one or more of Mo6S8, TiS2, V2O5, sodium iron pyrophosphate, and Prussian blue cathode material; the mass ratio of the solid magnesium electrolyte, cathode active material, and conductive agent is 5-40:60-95:0-10. Preferably, it is 70-80:20-30:0-5.
[0016] The composite cathode is composed of a mixture of the cathode active material Mo6S8 and the solid electrolyte Mg(AlCl4)2·2NH3BH3 in a mass ratio of 80:20.
[0017] A solid-state magnesium battery includes a positive electrode material, a solid electrolyte, and a negative electrode, wherein the solid electrolyte contains the ammonia borane-modified chloride solid-state magnesium electrolyte.
[0018] Alternatively, the positive electrode material may be the magnesium battery composite positive electrode material.
[0019] A method for preparing the solid magnesium battery involves pressing the solid magnesium electrolyte into a solid electrolyte sheet, then sequentially adding a positive electrode material and a negative electrode material to both sides of the solid electrolyte sheet, and then applying pressure to obtain the solid magnesium battery.
[0020] Furthermore, the solid electrolyte is first pressed into a solid electrolyte sheet (such as a circular sheet with a diameter of 10 mm). Then, the composite positive electrode material is added to one side of the solid electrolyte sheet and pressure is applied appropriately (1-100 MPa) to form a positive electrode. The negative electrode material is added to the other side and pressure is applied (1-100 MPa) to form a negative electrode. Finally, a certain pressure (1-50 MPa) is applied to assemble the solid battery.
[0021] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0022] 1. This invention utilizes the interaction between ammonia borane and magnesium tetrachloroaluminate to form a magnesium ion (Mg) 2+ ) and tetrachloroaluminate anion (AlCl4) - The framework network structure, which connects magnesium ions and ammonia borane small molecules (NH3BH3), exhibits excellent magnesium ion conductivity (room temperature ionic conductivity >10). -4 The ammonia borane-magnesium tetrachloroaluminate composite solid magnesium electrolyte exhibits better high-voltage stability compared to the traditional magnesium borohydride system. A solid magnesium metal secondary battery developed based on this ammonia borane-magnesium tetrachloroaluminate composite solid magnesium electrolyte achieved normal charge-discharge operation at room temperature.
[0023] 2. The raw materials used in this invention are readily available, the preparation method is simple to operate, the product performance is easy to control, and the production efficiency is high, which is conducive to large-scale production. It can also be matched with high-voltage cathode materials and is conducive to promoting the successful industrialization of solid magnesium metal secondary batteries. Attached Figure Description
[0024] Figure 1 The image shows the XRD results of Mg(AlCl4)2 powder in Comparative Example 1.
[0025] Figure 2The graph shows the EIS test results of Mg(AlCl4)2 powder tablets after compression in Comparative Example 1.
[0026] Figure 3 The image shows the XRD results of Mg(AlCl4)2·0.5NH3BH3 in Example 1.
[0027] Figure 4 The graph shows the EIS test results of the Mg(AlCl4)2·0.5NH3BH3 solid electrolyte in Example 1.
[0028] Figure 5 The image shows the XRD results of Mg(AlCl4)2·1.0NH3BH3 in Example 2.
[0029] Figure 6 The graph shows the EIS test results of the Mg(AlCl4)2·1.0NH3BH3 solid electrolyte in Example 2.
[0030] Figure 7 The image shows the XRD results of Mg(AlCl4)2·2.0NH3BH3 in Example 3.
[0031] Figure 8 The graph shows the EIS test results of the Mg(AlCl4)2·2.0NH3BH3 solid electrolyte in Example 3.
[0032] Figure 9 The image shows the XRD results of Mg(AlCl4)2·3.0NH3BH3 in Example 4.
[0033] Figure 10 The graph shows the EIS test results of the Mg(AlCl4)2·3.0NH3BH3 solid electrolyte in Example 4.
[0034] Figure 11 The graph shows the battery test results of the Mg(AlCl4)2·3.0NH3BH3 solid electrolyte in Example 5;
[0035] Figure 12 The graph shows the battery test results of the Mg(AlCl4)2·3.0NH3BH3 solid electrolyte in Example 6. Detailed Implementation
[0036] Exemplary embodiments of the present disclosure will now be described in more detail with reference to the accompanying drawings. While exemplary embodiments of the present disclosure are shown in the drawings, it should be understood that the present disclosure may be implemented in various forms and should not be limited to the embodiments set forth herein. Rather, these embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the disclosure to those skilled in the art.
[0037] Comparative Example 1: Synthesis and Performance Testing of Mg(AlCl4)2 Powder
[0038] (1) Preparation of Mg(AlCl4)2 powder
[0039] Accurately weigh MgCl2 and AlCl3 into a ball mill jar in an argon-filled glove box, with a molar ratio of 1:2. Add zirconia grinding beads with a mass 20 times the total mass of the raw materials, seal the ball mill jar, and protect it with an argon atmosphere. Ball mill at 300 rpm for 6 hours to mix MgCl2 and AlCl3 evenly. Seal the mixed MgCl2 and AlCl3 powder in an argon atmosphere, then place it in a tube furnace and sinter at 600℃ for 12 hours. After cooling, remove the synthesized Mg(AlCl4)2 bulk material from the glove box, and finally grind it into powder using a mortar and pestle for later use.
[0040] (2) Phase characterization of Mg(AlCl4)2 powder
[0041] XRD analysis was performed on Mg(AlCl4)2 powder under conditions of H2O and O2 isolation. The results are as follows: Figure 1 As shown, a comparison with the standard PDF card of Mg(AlCl4)2 reveals that high-purity Mg(AlCl4)2 powder was successfully synthesized.
[0042] (3) Ionic conductivity test of Mg(AlCl4)2
[0043] The prepared Mg(AlCl4)2 powder was placed in a 10 mm diameter polytetrafluoroethylene mold, and then the electrolyte powder was pressed into a tablet using a 10 mm diameter stainless steel column at a pressure of 6.0 MPa. After sealing, electrochemical impedance spectroscopy was performed. The test results are as follows: Figure 2 As shown, the measured ionic conductivity at room temperature is 2.4 × 10⁻⁶. -10 S cm -1 .
[0044] Example 1: Preparation and Ionic Conductivity Testing of Solid Electrolyte Mg(AlCl4)2·0.5NH3BH3
[0045] (1) Preparation of solid electrolyte Mg(AlCl4)2·0.5NH3BH3
[0046] Accurately weigh Mg(AlCl4)2 and NH3BH3 into a ball mill jar in an argon glove box, with a molar ratio of 1:0.5. Then add zirconia grinding beads with a mass 20 times the total mass of the raw materials, seal the ball mill jar, and protect it with an argon atmosphere. Ball mill at 300 rpm for 12 hours to obtain solid electrolyte Mg(AlCl4)2·0.5NH3BH3 powder. Figure 3 As shown, the XRD results prove that the diffraction peak signals of Mg(AlCl4)2·0.5NH3BH3 are significantly different from those of the raw materials Mg(AlCl4)2 and NH3BH3, and the diffraction peak intensities are significantly weakened, indicating that the crystallinity of the synthesized Mg(AlCl4)2·0.5NH3BH3 powder is worse.
[0047] (2) Ionic conductivity test of Mg(AlCl4)2·0.5NH3BH3
[0048] The prepared electrolyte powder was placed in a 10 mm diameter polytetrafluoroethylene mold, and then pressed into a tablet using a 10 mm diameter iron cylinder at a pressure of 3.0 MPa. After sealing, electrochemical impedance spectroscopy was performed. The test results are as follows. Figure 4 As shown, the measured ionic conductivity at room temperature is 8.9 × 10⁻⁶. -8 S cm -1 .
[0049] Example 2: Preparation and Ionic Conductivity Testing of Solid Electrolyte Mg(AlCl4)2·1.0NH3BH3
[0050] (1) Preparation of solid electrolyte Mg(AlCl4)2·1.0NH3BH3
[0051] Accurately weigh Mg(AlCl4)2 and NH3BH3 into a ball mill jar in an argon glove box, with a molar ratio of 1:1. Add zirconia grinding beads with a mass 20 times the total mass of the raw materials, seal the ball mill jar, and ensure an argon atmosphere inside. Ball mill at 300 rpm for 12 hours to obtain solid electrolyte Mg(AlCl4)2·1.0NH3BH3 powder. Figure 5 As shown, the XRD results demonstrate that the diffraction peak signals of Mg(AlCl4)2·1.0NH3BH3 are significantly different from those of the raw materials Mg(AlCl4)2 and NH3BH3, and the diffraction peak intensities are further reduced, indicating that the synthesized Mg(AlCl4)2·1.0NH3BH3 powder is further amorphous.
[0052] (2) Ionic conductivity test of Mg(AlCl4)2·1.0NH3BH3
[0053] The prepared electrolyte powder was placed in a 10 mm diameter polytetrafluoroethylene mold, and then pressed into a tablet using a 10 mm diameter iron cylinder at a pressure of 3.0 MPa. After sealing, electrochemical impedance spectroscopy was performed. The test results are as follows. Figure 6 As shown, the measured ionic conductivity at room temperature is 6.6 × 10⁻⁶. -6 S cm -1 .
[0054] Example 3: Preparation and Ionic Conductivity Testing of Solid Electrolyte Mg(AlCl4)2·2.0NH3BH3
[0055] (1) Preparation of solid electrolyte Mg(AlCl4)2·2.0NH3BH3
[0056] Accurately weigh Mg(AlCl4)2 and NH3BH3 into a ball mill jar in an argon glove box, with a molar ratio of 1:2. Add zirconia grinding beads with a mass 20 times the total mass of the raw materials, seal the ball mill jar, and ensure an argon atmosphere inside. Ball mill at 300 rpm for 12 hours to obtain solid electrolyte Mg(AlCl4)2·2.0NH3BH3 powder. Figure 7 As shown, the XRD results prove that the diffraction peak signals of Mg(AlCl4)2·2.0NH3BH3 are significantly different from those of the raw materials Mg(AlCl4)2 and NH3BH3, and there are no obvious diffraction peak signals, indicating that the material has been basically amorphous.
[0057] (2) Ionic conductivity test of Mg(AlCl4)2·2.0NH3BH3
[0058] The prepared electrolyte powder was placed in a 10 mm diameter polytetrafluoroethylene mold, and then pressed into a tablet using a 10 mm diameter iron cylinder at a pressure of 1.0 MPa. After sealing, electrochemical impedance spectroscopy was performed. The test results are as follows: Figure 8 As shown, the measured ionic conductivity at room temperature is 2.4 × 10⁻⁶. -4 S cm -1 .
[0059] Example 4: Preparation and Ionic Conductivity Testing of Solid Electrolyte Mg(AlCl4)2·3.0NH3BH3
[0060] (1) Preparation of solid electrolyte Mg(AlCl4)2·3.0NH3BH3
[0061] Accurately weigh Mg(AlCl4)2 and NH3BH3 into a ball mill jar in an argon glove box, with a molar ratio of 1:3. Add zirconia grinding beads with a mass 20 times the total mass of the raw materials, seal the ball mill jar, and ensure an argon atmosphere inside. Ball mill at 300 rpm for 12 hours to obtain solid electrolyte Mg(AlCl4)2·3.0NH3BH3 powder. Figure 9 As shown, the XRD results prove that the diffraction peak signals of Mg(AlCl4)2·3.0NH3BH3 are significantly different from those of the raw materials Mg(AlCl4)2 and NH3BH3, and there are no obvious diffraction peak signals, indicating that the material has been completely amorphous.
[0062] (2) Ionic conductivity test of Mg(AlCl4)2·3.0NH3BH3
[0063] The prepared electrolyte powder was placed in a 10 mm diameter polytetrafluoroethylene mold, and then pressed into a tablet using a 10 mm diameter iron cylinder at a pressure of 1.0 MPa. After sealing, electrochemical impedance spectroscopy was performed. The test results are as follows: Figure 10 As shown, the measured ionic conductivity at room temperature is 7.8 × 10⁻⁶. -4 S cm -1 .
[0064] Example 5: Application of solid electrolyte Mg(AlCl4)2·2.0NH3BH3 in solid magnesium metal secondary batteries
[0065] (1) Preparation of composite cathode materials
[0066] The positive electrode active material Mo6S8 and the solid electrolyte Mg(AlCl4)2·2.0NH3BH3 were weighed at a mass ratio of 80:20 and manually ground in a mortar for 30 minutes to mix the materials evenly, thus obtaining the composite positive electrode material.
[0067] (2) Assembly of all-solid-state batteries
[0068] First, 100 mg of Mg(AlCl4)2·3.0NH3BH3 solid electrolyte was added to a 10 mm diameter mold and pressurized to 1.0 MPa. Then, 10 mg of composite positive electrode material was added to the positive electrode side and pressurized to 2.0 MPa, and a 10 mm diameter magnesium metal disc was added to the negative electrode side and pressurized to 2.0 MPa. All of the above processes were carried out in an argon glove box.
[0069] (3) Testing of all-solid-state batteries
[0070] The test temperature was 25℃, and the voltage range for the constant current charge-discharge test was 0.1~2.0V (vs. Mg). The charge-discharge curve of the all-solid-state battery at 15mAh / g is shown below. Figure 11 As shown, the discharge specific capacity of this battery is ~90mAh / g.
[0071] Example 6: Application of solid electrolyte Mg(AlCl4)2·3.0NH3BH3 in high-voltage solid magnesium metal secondary batteries
[0072] (1) Preparation of composite cathode materials
[0073] The high-voltage positive electrode active material V2O5 and the solid electrolyte Mg(AlCl4)2·3.0NH3BH3 were weighed at a mass ratio of 80:20 and manually ground in a mortar for 30 minutes to mix the materials evenly, thus obtaining the composite positive electrode material.
[0074] (2) Assembly of high-voltage all-solid-state batteries
[0075] First, 100 mg of Mg(AlCl4)2·2.0NH3BH3 solid electrolyte was added to a 10 mm diameter mold and pressurized to 1.0 MPa. Then, 10 mg of composite positive electrode material was added to the positive electrode side and pressurized to 2.0 MPa, and a 10 mm diameter magnesium metal disc was added to the negative electrode side and pressurized to 2.0 MPa. All of the above processes were carried out in an argon-filled glove box.
[0076] (3) Testing of all-solid-state batteries
[0077] The test temperature was 25℃, and the voltage range for the constant current charge-discharge test was 0.4~2.6V (vs. Mg). The charge-discharge curve of the all-solid-state battery at 20mAh / g is shown below. Figure 12 As shown, the discharge specific capacity of the battery is ~122mAh / g, which fully demonstrates the compatibility of the Mg(AlCl4)2·3.0NH3BH3 solid electrolyte with high-voltage cathode material.
[0078] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A magnesium chloride solid electrolyte modified with ammonia borane, characterized in that: The chloride solid magnesium electrolyte is a complex of magnesium tetrachloroaluminate (Mg(AlCl4)2) and ammonia borane (NH3BH3), with the chemical formula Mg(AlCl4)2·xNH3BH3, where 0.1≤x≤5.
2. A method for preparing the ammonia borane-modified chloride solid magnesium electrolyte according to claim 1, characterized in that: Magnesium tetrachloroaluminate (Mg(AlCl4)2) and ammonia borane (NH3BH3) were weighed and mixed according to the stoichiometric ratio of the elements in the target solid electrolyte. After mixing, the mixture was ball-milled to obtain Mg(AlCl4)2·xNH3BH3.
3. The method for preparing ammonia borane-modified chloride solid magnesium electrolyte according to claim 2, characterized in that: The weighing and ball milling of the magnesium tetrachloroaluminate (Mg(AlCl4)2) and ammonia borane (NH3BH3) were carried out in an inert gas atmosphere, and the contents of O2 and H2O were both less than 0.01 ppm.
4. The method for preparing ammonia borane-modified chloride solid magnesium electrolyte according to claim 2 or 3, characterized in that: The ball mill operates at a speed of 100–800 rpm for a time of 0.5–50 h.
5. The method for preparing the ammonia borane-modified chloride solid magnesium electrolyte according to claim 4, characterized in that: The ball mill rotates at a speed of 200–400 rpm and the milling time is 10–30 h.
6. The application of the ammonia borane-modified chloride solid magnesium electrolyte according to claim 1, characterized in that: The chloride solid magnesium electrolyte is used in the preparation of magnesium electrolytes as magnesium ion transport media for solid magnesium batteries.
7. A magnesium battery composite cathode material, the cathode material comprising an electrolyte and a cathode active material, characterized in that: The electrolyte is the ammonia borane-modified chloride solid magnesium electrolyte as described in claim 1.
8. The magnesium battery composite cathode material according to claim 7, characterized in that: The magnesium battery composite cathode material may also contain a conductive agent; wherein the conductive agent is one or more of conductive carbon black, Super-P, Ketjen black, acetylene black, and carbon nanotubes; the cathode active material is one or more of Mo6S8, TiS2, V2O5, sodium iron pyrophosphate, and Prussian blue cathode; the mass ratio of the solid magnesium electrolyte, cathode active material, and conductive agent is 5-40:60-95:0-10.
9. A solid-state magnesium battery, comprising a positive electrode material, a solid electrolyte, and a negative electrode, characterized in that: The solid electrolyte is the ammonia borane-modified chloride solid magnesium electrolyte as described in claim 1; Alternatively, the positive electrode material may be the magnesium battery composite positive electrode material as described in claim 7.
10. A method for preparing a solid-state magnesium battery according to claim 9, characterized in that: The solid magnesium electrolyte of claim 1 is pressed into a solid electrolyte sheet, and then a positive electrode material and a negative electrode material are added to both sides of the solid electrolyte sheet in sequence, and then pressure is applied to obtain the solid magnesium battery.
